The effect of polyphosphate kinase deficiency on antibiotic production in Streptomyces coelicolor - Yalym, Y.; Doruk, T.; Savap, UE.; Tunca, S. (Wiley-Blackwell Publishing, Inc, 2010)
[No abstract available]
35th Congress of the Federation-of-European-Biochemical-Societies -- JUN 26-JUL 01, 2010 -- Gothenburg, SWEDEN